Deposit Insurance Regulatory forbearance and Economic Growth : Implications for the Japanese Banking Crisis - Kletzer, Kenneth (IMF Working Papers; Working Paper ;, 2005)
An endogenous growth model with financial intermediation demonstrates how deposit insurance and prudential regulatory forbearance lead to banking crises and growth declines. The model assumptions are based on features of the Japanese financial system and regulation. The model demonstrates how banking and growth crises can evolve under perfect foresight. The dynamics for economic aggregates and asset prices predicted by the model are shown to be generally consistent with the experience of the Japanese economy and financial system through the 1990s. We also test our maintained hypothesis of rational expectations using asset price data for Japan over the 1980s and 1990s.